European Union advisory and consultative institutions as consumer policy actors - Malczyńska-Biały, Mira (Polityka i Społeczeństwo, 2025)
This article aims to present the core functions of EU advisory and consultative institutions as actors in European Union consumer policy. It describes the European Economic and Social Committee and EU non-governmental consumer organisations involved in developing and implementing European Union consumer policy. In the context of safeguarding consumer interests at the EU level, these institutions serve an advisory and consultative role. This role includes providing advice, information, and standardisation activities, primarily by emphasising the need to introduce suitable legal measures for consumer safety.